การวิเคราะห์อภิมานคุณภาพของแบบสอบหลายตัวเลือก ที่มีรูปแบบของแบบสอบบริบทของแบบสอบ และวิธีการตรวจให้คะแนนต่างกัน - ไชยยศ ไพวิทยศิริธรรม (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The purpose of this research was to synthesize research about the quality of multiple-choice tests, comprising of reliability, validity, item difficulty and power of discrimination with different test formats, test contexts, scoring methods and test type by using Hunter’s meta-analysis method. Ninety six research reports to be synthesized consisted of 92 experimental research and 4 correlational research, published in 1968-1999 from three libraries: namely Chulalongkorn university, Srinakharinwirot university and Kasetsart university. The database of this research consisted of 1,837 standard indices with were divided into 777 reliability coefficients, 461 validity coefficients, 283 indices of item difficulty and 316 indices of power of discrimination. The data analysis employed descriptive statistic and ANOVA. The research results were as follows: 1. The average of reliability was .713 and the minimum and maximum were .020 and .999 respectively. The moderator variables which could significantly explain the difference in reliability and its value that gave maximum subgroup means were as follow: choice arrangement -high to low value arrangement (.775); item ordering -low to high learning behavior ordering (.818); scoring method -optimal scoring weighted by examinee’s ability (.951) and test type -completion type.(.852) 2. The average of validity was .528 and the minimum and maximum were .005 and .950 respectively. The moderator variables which could significantly explain the difference in validity and its value that gave maximum subgroup means were as follow: distractor construction -student’s mistake based distractor (.691); item ordering -low to high learning behavior ordering (.623) and scoring method -Samran Mejang’s scoring method.(.756) 3. The average of item difficulty was .474 and the minimum and maximum were .100 and .871 respectively. The moderator variables which could significantly explain the difference in item difficulty and its value that gave middle subgroup means were as follow: item ordering -random ordering (.484); scoring method -scoring adjusted for guessing (.497) and test type -multiple-choice type.(.538) 4. The average of power of discrimination was .433 and the minimum and maximum were .125 and .838 respectively. The moderator variables which could significantly explain the difference in power of discrimination and its value that gave maximum subgroup means were as follow: distractor construction -student’s mistake based, distractor (.550) and scoring method -Anan Srisopa’s scoring method.(.693)